ANALISIS PENGARUH KEPRIBADIAN INDIVIDU, KOMITMEN ORGANISASI, DAN KEPUASAN KERJA TERHADAP OCB (ORGANIZATIONAL CITIZENSHIP BEHAVIOUR) PADA KARYAWAN KANTOR UPPD SAMSAT KABUPATEN CILACAP - Nurul Hasanah; Guntoro Guntoro; Wahyu Alfriani (AmaNU: Jurnal Manajemen dan Ekonomi, 2021)
The research objective was to analyze the effect of individual personality, organizational commitment, and job satisfaction on OCB (Organizational Citizenship Behavior) in UPPD/SAMSAT Office Employees, Cilacap Regency. The hypothesis proposed is Individual Personality, Organizational Commitment, and Job Satisfaction have an influence on Organizational Citizenship Behavior (OCB). This study used a survey method and data were collected through a questionnaire. The number of samples is 40 people or using the census method. The analytical tools used are Multiple Linear Regression Analysis and Partial Test (t test). The results showed that individual personality, organizational commitment, and job satisfaction had a significant effect on OCB (Organizational Citizenship Behavior) as evidenced by the t-value of the three variables greater than the t-table value.